Prediction of organophosphorus insecticide-induced intermediate syndrome with stimulated concentric needle single fibre electromyography - Alahakoon, Chanika (PLoS One, 2018)
BACKGROUND: Deliberate self-poisoning (DSP) using organophosphorus (OP) insecticides are a common clinical problem in Asia. OPs inhibit acetylcholine esterase (AChE), leading to over-activity of muscarinic and nicotinic cholinergic circuits. Intermediate syndrome (IMS) is mediated via prolonged nicotinic receptor stimulation at the neuromuscular junction and its onset is between 24–96 hours post ingestion. The aims of the present study were 1) to investigate whether neuromuscular junction dysfunction within the first 24 hours following exposure, quantified by jitter in single fibre electromyography (SfEMG), can predict IMS, and 2) to compare the changes in SfEMG jitter over the course of the illness among patients who developed IMS (IMS+) and those who did not (IMS-). METHODS AND FINDINGS: We conducted a prospective cohort study in a tertiary care hospital in Sri Lanka on 120 patients admitted between September 2014 and August 2016 following DSP by OP insecticides viz., profenofos 53, phenthoate 17, diazinon 13, chlorpyrifos 5, others 12, unknown 20. SfEMG was performed every second day during hospitalization. Exposure was confirmed based on the history and red blood cell AChE assays. IMS was diagnosed in patients who demonstrated at least three out of four of the standard IMS criteria: proximal muscle weakness, bulbar muscle weakness, neck muscle weakness, respiratory paralysis between 24–96 hours post ingestion. Respiratory failure requiring intubation occurred in 73 out of 120 patients; 64 of these were clinically diagnosed with IMS. Of the 120 patients, 96 had repeated SfEMG testing, 67 of them being tested within the first 24 hours. Prolonged jitter (>33.4μs) within the first 24 hours was associated with greatly increased risk of IMS (odds ratio = 8.9, 95% confidence intervals = 2.4–29.6, p = 0.0003; sensitivity 86%, specificity 58%). The differences in jitter between IMS+ and IMS- patients remained significant for 72 hours and increased jitter was observed in some patients for up to 216 hours. For intubated patients, the median time for jitter to normalize and median time to extubate were similar, and the two variables had a moderate positive correlation (r = 0.49, P = 0.001). CONCLUSIONS: Prolonged jitter recorded with SfEMG <24 hours of ingestion of an OP strongly correlates with subsequent occurrence of IMS. The time course of electrophysiological recovery of the NMJ was similar to the time course of respiratory recovery in IMS patients.